Study Kekuatan Bending Dan Struktur Mikro Komposit Polyethylene Yang Diperkuat Oleh Hybrid Serat Sisal Dan Karung Goni - I Gede Widiartha; Nasmi Herlina Sari; S. Sujita (Universitas Mataram, 2012)
AbstractThe purpose of this study is to investigate and study the mechanical properties of polyethylene strukrur micro hybrid composites reinforced by fibers sisal and jute sacks.Preparation of composites by hand lay-up method with a ratio of fiber volume fraction of sisal and jute sacks 30%: 0%, 20%: 10%, 15%: 15%, 10%: 20%, 0%: 30%. With unidirectional sisal fiber orientation and fiber length random burlap gunny sack fibers 2 cm. Specimen testing is performed with a standard bending test ASTM D790, and microstructure.Test results obtained from the average bending strength of composites with high fiber volume ratio fraksin 30%: 0% is 74.43 Mpa. While the lowest average for bending strength found in composites with fiber volume fraction of 0%: 30%, the bending strength of 32.21 MPa. Therefore we can conclude the increasing volume fraction of sisal fiber with unidirectional fiber orientation, the higher the bending strength of its appeal and reverse the growing volume of burlap fibers with random orientation of the fibers feeding the lower the bending strength and the strength.